Dissecting Optical Response and Molecular Structure of Fluorescent Proteins With Non-canonical Chromophores - Oscar, Breland G.; Zhu, Liangdong; Wolfendeen, Hayati; Rozanov, Nikita D.; Chang, Alvin; Stout, Kenneth T.; Sandwisch, Jason W.; Porter, Joseph J.; Mehl, Ryan A.; Fang, Chong (Frontiers in Molecular Biosciences, 2020)
Tracking the structural dynamics of fluorescent protein chromophores holds the key to unlocking the fluorescence mechanisms in real time and enabling rational design principles of these powerful and versatile bioimaging probes. By combining recent chemical biology and ultrafast spectroscopy advances, we prepared the superfolder green fluorescent protein (sfGFP) and its noncanonical amino acid (ncAA) derivatives with a single chlorine, bromine, and nitro substituent at the ortho site to the phenolate oxygen of the embedded chromophore, and characterized them using an integrated toolset of femtosecond transient absorption and tunable femtosecond stimulated Raman spectroscopy (FSRS), aided by quantum calculations of the vibrational normal modes. A dominant vibrational cooling time constant of ~4 ps and 11 ps is revealed in Cl-GFP and Br-GFP, respectively, facilitating a ~30% and 12% increase of the fluorescent quantum yield versus the parent sfGFP. Similar time constants were also retrieved from the transient absorption spectra, substantiating the correlated electronic and vibrational motions on the intrinsic molecular timescales. Key carbon-halogen stretching motions coupled with phenolate ring motions of the deprotonated chromophores at ca. 908 and 890 cm-1 in Cl-GFP and Br-GFP exhibit enhanced activities in the electronic excited state and blue-shift during a distinct vibrational cooling process on the ps timescale. The retrieved structural dynamics change due to targeted site-specific halogenation of the chromophore thus provides an effective means to design new GFP derivatives and enrich the bioimaging probe toolset for life and medical sciences.